OPTIMIZATION OF CAT 374D L ARM EXCAVATOR STRUCTURE TOPOLOGY DESIGN USING FINITE ELEMENT METHODS - Suryo, Sumar Hadi; Harto, Harto; Yunianto, Bambang (ROTASI, 2020)
In the current era of development, infrastructure is the driving wheel of economic growth. Company manufacturer of construction which is headquartered in Illinois, United States of America, namely Caterpillar Inc. is a large manufacturer of construction equipment that operates more than 157 countries. Excavators are heavy equipment and are usually used for excavation. During the operation of extracting the unknown forces resistive offered by the terrain to the bucket teeth. In this study discusses the design optimization of the arm of the excavator to produce a design that is lightweight but still retains his strength, arm of the excavator is R4.67m CAT 374D L. Process optimization on the arm of the excavator to apply the concept of optimization the topology. The method includes the determination of the type of material Hardox400. The analysis was then performed linear static using the finite element method to see the maximum voltage that occurs on the arm of the excavator, the value of the stress von Mises amounted to 350.9 MPa. Further optimization of the topology by selecting some of the variations in area design which produces a reduction of mass of 4000 kg became 3852 kg. The reduction of mass causes a change in voltage that occurs on the arm of the excavator to be 340.9 MPa and a safety factor of design optimization to achieve 2.88 is still in a safe condition.